Analisis Pengaruh Kinerja Lingkungan, Pertumbuhan Aset, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Jagad Bayu Seto; Murtanto (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the effect of Environmental Performance, Asset Growth and Company Size on Company Value. The data used is secondary data obtained from the Indonesia Stock Exchange. The sampling technique uses a purposive sampling approach, namely the sampling method based on certain criteria set by the researcher as objective. The data analysis technique was carried out using multiple regression analysis using the SPSS 23.0 application. This study uses oil, gas and coal sector companies listed on the Indonesia Stock Exchange for the period 2021-2023, totaling 72 samples. The results of hypothesis testing conducted in this study indicate that environmental performance has a positive effect on firm value while asset growth and company size have no effect on the value of companies in the oil, gas and coal sectors.